2018
DOI: 10.1152/physiolgenomics.00002.2018
|View full text |Cite
|
Sign up to set email alerts
|

Adipose transcriptome analysis provides novel insights into molecular regulation of prolonged fasting in northern elephant seal pups

Abstract: The physiological and cellular adaptations to extreme fasting in northern elephant seals ( Mirounga angustirostris, NES) are remarkable and may help to elucidate endocrine mechanisms that regulate lipid metabolism and energy homeostasis in mammals. Recent studies have highlighted the importance of thyroid hormones in the maintenance of a lipid-based metabolism during prolonged fasting in weaned NES pups. To identify additional molecular regulators of fasting, we used a transcriptomics approach to examine chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
7
1
Order By: Relevance
“…These results are consistent with the necessary reduction in energy expenditure during hibernation 26 . In contrast to the large number of DE genes we found in adipose in bears, recent studies in captive dwarf lemurs and elephant seal pups found fewer than 100 DE genes between physiological states similar to the active (feeding) and hibernation (torpid or fasting) seasons 27,28 . In lemurs, that number increased to 377 DE genes when comparing fattening (similar to bear hyperphagia) and torpid states 29 .…”
Section: Discussioncontrasting
confidence: 93%
“…These results are consistent with the necessary reduction in energy expenditure during hibernation 26 . In contrast to the large number of DE genes we found in adipose in bears, recent studies in captive dwarf lemurs and elephant seal pups found fewer than 100 DE genes between physiological states similar to the active (feeding) and hibernation (torpid or fasting) seasons 27,28 . In lemurs, that number increased to 377 DE genes when comparing fattening (similar to bear hyperphagia) and torpid states 29 .…”
Section: Discussioncontrasting
confidence: 93%
“…Using the proportions of different saturated/unsaturated fatty acids or the proportion of triaclyglycerols to wax esters, for example, could also be investigated as a more reliable marker. Proteomic and transcriptomic approaches to examine changes in proteins of interest and the use of gene expression profiles in blubber tissue are also being investigated to identify important markers and regulators of lipid metabolism and energy homeostasis (Kershaw, Botting, Brownlow, & Hall, 2018;Khudyakov, Champagne, Meneghetti, & Crocker, 2017;Martinez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of genes and their interactions play pivotal roles in maintaining adipose tissue function and properties including lipid, glucose and caloric metabolism, regulation to adipocyte size and lineage commitment, epigenetic and gene transcription regulatory activities, and cell cycle regulation [86,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105] (Supplementary Figure 4). For instance, the Gsk3b gene maintains adipogenic lineage commitment during differentiation of mouse embryonic fibroblasts [84] and shows the second-highest number of degrees in the PPI network.…”
Section: Discussionmentioning
confidence: 99%